2011
DOI: 10.1007/s00170-011-3695-6
|View full text |Cite
|
Sign up to set email alerts
|

A high-accuracy trajectory following controller for pneumatic devices

Abstract: The use of pneumatic devices is widespread among different industrial fields, in tasks like handling or assembly. Pneumatic systems are low-cost, reliable, and compact solutions. However, its use is typically restricted to simple tasks due to the poor performance achieved in applications where accurate motion control is required. This paper presents a novel nonlinear controller, using neural network-based models, that allows the use of common industrial servopneumatic components in applications where fine traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Furthermore, the controlled system was highly robust to parameter variation since high accuracy results were obtained without any controller retuning even though the payload varied from 2.6 to 13.1 kg. Using an enhanced version of the controller developed in [18], the authors of this study also showed in [19] that good results may be achieved in the micrometre range. Indeed, in [19], the positioning error obtained from a control perspective was only limited by the encoder resolution, 1 μm, in any position of the piston stroke and when carrying loads of 3 and 8 kg, without any controller retuning.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, the controlled system was highly robust to parameter variation since high accuracy results were obtained without any controller retuning even though the payload varied from 2.6 to 13.1 kg. Using an enhanced version of the controller developed in [18], the authors of this study also showed in [19] that good results may be achieved in the micrometre range. Indeed, in [19], the positioning error obtained from a control perspective was only limited by the encoder resolution, 1 μm, in any position of the piston stroke and when carrying loads of 3 and 8 kg, without any controller retuning.…”
Section: Introductionmentioning
confidence: 92%
“…This was the path followed by the authors of this study in previous works [18,19]. In fact, in [18,19], the disturbances were tackled using a friction model to handle friction disturbance and a sliding-based control law to handle not only the payload variation but also the friction model errors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations